Effects of dietary L-Ascorbyl-2-Polyphosphate as a source of vitamin C on growth indices in beluga sturgeon (Huso huso L.) - Soltani, M.; Falahatkar, B.; Pourkazemi, M.; Abtahi, B.; Kalbassi, M.R.; Mohseni, M. (2008)
Six diets supplemented with 0, 100, 200, 400, 800, and 1600mg/kg L-Ascorbyl-2-Polyphosphate (APP) as vitamin C, were fed to juvenile beluga sturgeon in three replicates for 16 weeks. Fifty five fish with an average weight 38.1 plus or minus 0.5g were distributed to each tank after adaptation to the experimental diets. Most of the growth performance indices at week 4 indicated significant differences (P0.05), except in CF and PER (P0.05). The survival was affected by dietary treatment at week 4 (P0.05). No deficiency sign was observed during the trial. Results of this study indicated that vitamin C can have remarkable effects on growth indices in different growth periods. Therefore, regarding the effects of vitamin C on the growth indices and in the fish weight range used in this study, 100-200mg/kg vitamin C (APP) can be considered as the optimum level for rearing the fish. Published